Iowa Birdline update, December 12, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for December 12, 1994. Highlights of the update include sightings of a Bohemian Waxwing as well as several species of Gulls, including a first winter Mew Gull, an adult Lesser Black-backed Gull, a first winter Glaucous Gull, and a first winter Thayer's Gull. Also included are handwritten notes for the next week's update with sightings of a Say's Phoebe, Trumpeter Swans, an Eastern Bluebird, and a flock of Snow Buntings. Epson - sheet feed/flatbed